Synthesis of Functionalized 1,4-Dioxanes with an Additional (Hetero)Aliphatic Ring - Bondarenko, Andriy V.; Tolmachev, Andrey A.; Vashchenko, Bohdan V.; Grygorenko, Oleksandr O. (Synthesis, 2018)
An approach to the preparation of 2-mono-, 2,2- and 2,3-disubstituted 1,4-dioxane derivatives is described. The reaction sequence commences from readily available epoxides, in most cases prepared via the Corey–Chaikovsky reaction of the corresponding aldehydes and ketones. The key step of the method is epoxide ring opening with ethylene glycol monosodium salt, followed by further cyclization of the diols obtained. The utility of the approach was demonstrated by multigram preparation of novel functionalized 1,4-dioxanes bearing additional cycloalkane, piperidine or pyrrolidine rings, mostly spirocyclic compounds, which are advanced building blocks for medicinal chemistry.
Keywords: oxygen heterocycles; 1,4-dioxane; spiro compounds; building blocks; oxirane